'Massacre (1934): Hollywood's Overlooked Adaptation on the Native American Genocide'. (23rd August 2017) - Kennelly, Kate Meredith
Abstract: In 1931, Robert Gessner published Massacre: A Survey of Today's American Indian, one of the earliest, most overlooked indictments of the Native American genocide to be adapted to the screen. Warner Bros.' Massacre (Alan Crosland, 1934) is a dramatised version of his non-fiction account, focusing on a Sioux Indian named Joe Thunderhorse who returns to his reservation and finds it overrun by abusive government officials. When his sister is raped and kidnapped, he appeals to the Commissioner of Indian Affairs, who swiftly takes up his case and helps him secure the conviction of the reservation superintendent in federal court. Massacre (1934) received little public attention upon its release. In the decades since, it has gone unexamined by scholars, aside from a few production studies that have pointed to the effects of New Deal ideology and Hays Office censorship in manufacturing the film's simplistically triumphant conclusion. So far, no scholar has undertaken an adaptation studies approach to determine precisely how much of the book's anti-government criticism the film retains. While its ending diverges from Gessner's conclusion that the government remained unresponsive to Native Americans' pleas for justice, this should not eclipse the ways in which Massacre boldly conveys the author's unprecedented attack on the starvation, extortion, disease, and physical and sexual abuse perpetrated by the federal government's Bureau of Indian Affairs.